2017
DOI: 10.1200/jco.2017.35.15_suppl.5018
|View full text |Cite
|
Sign up to set email alerts
|

Extended versus limited pelvic lymphadenectomy during radical prostatectomy for intermediate- and high-risk prostate cancer: Early outcomes from a randomized controlled phase III study.

Abstract: 5018 Background: The role of extended pelvic lymph node dissection (ePLND) in treating prostate cancer (PCa) patients remains controversial, mainly by the lack of RCTs. Methods: Patients with D'Amico intermediate or high risk PCa, absence of bone metastasis and no previous treatment were prospectively computer randomised to undergo extended or limited PLND (1:1) during radical prostatectomy. Limited PLND (lPLND) included the obturator chain bilaterally; ePLND involved bilaterally chains: obturator, external-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To date, randomized data have demonstrated a significant detection benefit for e-PLND/se-PLND over more limited dissections: gross lymph node yield is improved, and detectable lymph node metastases are increased (45)(46)(47). In a contemporary cohort from the randomized, phase III trial by Lestingi et al, (s)e-PLND yielded a median of 17 nodes versus 3 from l-PLND, and detected 6 times more nodal metastases (45). Nevertheless, despite the improved performance on staging and prognostication, no therapeutic benefit was garnered with similar rates of biochemical recurrence and increased complications.…”
Section: Potential Oncologic Benefitsmentioning
confidence: 99%
“…To date, randomized data have demonstrated a significant detection benefit for e-PLND/se-PLND over more limited dissections: gross lymph node yield is improved, and detectable lymph node metastases are increased (45)(46)(47). In a contemporary cohort from the randomized, phase III trial by Lestingi et al, (s)e-PLND yielded a median of 17 nodes versus 3 from l-PLND, and detected 6 times more nodal metastases (45). Nevertheless, despite the improved performance on staging and prognostication, no therapeutic benefit was garnered with similar rates of biochemical recurrence and increased complications.…”
Section: Potential Oncologic Benefitsmentioning
confidence: 99%
“…There was no benefit in biochemical recurrence (BCR), radiotherapy efficacy, androgen-deprivation therapy (ADT) efficacy, bone metastasis or mortality, and e-PLND significantly increased operative time, intraoperative bleeding volume, length of hospital stay and incidence of postoperative complications [29]. We believe that this is a high-level evidence-based medical research study, but we cannot deny the findings of all previous studies.…”
Section: The Relationship Between the Number Of Lymph Nodes Resected mentioning
confidence: 75%
“…Overall, the quality of the evidence was low, and the risk of bias high. Three randomised control trials were available, of which one was reported as conference abstracts only [8,9], and only 4 of the remaining studies were performed prospectively. Evidence is very mixed regarding risks and benefits.…”
Section: Risks and Benefitsmentioning
confidence: 99%